PENGARUH KEGIATAN EKSTRAKURIKULER PASUKAN PENGIBAR BENDERA(PASKIBRA) DALAM MEMBENTUK SIKAP NASIONALISME SISWADI SMP NEGERI 12 PEKANBARU - Rizka Fauziah; Sri Erlinda; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted as extracurricular activities motivated by the forces of the flag raisers aimed at forming attitudes of students due to the low nationalism nationalistic attitudes among students. The problems of this study was the effect of extracurricular activities troop flag raisers nationalism in shaping attitudes of students in SMP 12 Pekanbaru. As for the population and sample in this research that students who take paskibra extracurricular activities are 30 people with a sampling technique that technique saturated samples (total sampling). And Data collected through observations, questionnaires and interviews and technical literature. In analyzing the data using simple linear regression analysis. These results indicate that there are significant extracurricular activities troop flag raisers in shaping the attitudes of nationalism students in SMP 12 Pekanbaru, this is evidenced by a series of simple regression test between the variables X and Y, obtained F count = 9.753 and the value F table = 4 , 20 were obtained from the study of the distribution list F table with N = 30, at significance level of 5%, F count larger than F table or 9.753> 4.20 then Ho is rejected and Ha received significant meaning, there are significant extracurricular activities troop flag raisers in shaping students' attitudesnationalism in the State smp 12 pekanbaru.Keywords: Extracurricular Paskibra, Attitude NationalismRizka Fauziah¹, Sri Erlinda², Gimin³ Program Pancasila and Citizenship Education Study INFLUENCE OF FORCES EXTRACURRICULAR ACTIVITIESFLAG RAISERS